PERTANGGUNGJAWABAN PIDANA OLEH PENGURUS KORPORASI SEBAGAI PEMBERI PINJAMAN ONLINE ILEGAL - Ni Wayan Widya Pratiwi, (2023)
This study aims to the application of vicarious liability theory as criminal responsibility by corporations and the imposition of appropriate sanctions by perpetrators of corporate crimes in online loans as the primary regulation in POJK 77/2016. The type of research used is normative juridical, with a case approach, conceptual approach, and statutory approach. The data used is a type of secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Primary legal materials were obtained from laws and regulations, secondary legal materials were obtained from library studies and tertiary legal materials were obtained from dictionaries which explained primary and tertiary legal materials related to corporate criminal responsibility for online loans. Qualitative data analysis techniques and presented descriptively. The results of the study explained that a person who consciously (willens en wetness) causes legal consequences (voltooid delict/delict met matrieele omschrijving) and in his knowledge intentionally (opzet) commits an act which can be punished by him (strafbaar feit). As well as the provision of administrative sanctions in the form of criminal fines that are equivalent to returning the rights of victims in crimes that have an economic loss value and the need for risk mitigation in suppressing the growth of online loan cases.